2017
DOI: 10.1080/03079457.2017.1311990
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to vaccination and infection with Mycoplasma gallisepticum in turkeys

Abstract: Infection with Mycoplasma gallisepticum induces severe lymphoproliferative lesions in multiple sites along the respiratory tract in chickens and turkeys. These immunopathological responses have been well-characterized in chickens, but have not been studied closely in turkeys. The aim of the study described here was to examine the immune responses of turkeys after live vaccination and infection with M. gallisepticum. In a strain comparison study, the mean log antibody titre of birds exposed to an aerosol cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Infected poults with MG revealed insignificant decrease in IgA, IgG and IgM allover experimental period post infection Mycoplasma infection induced reduction in immune-globulin (Romero et al, 2001). Same change in immunoglobulin was reported by Wijesurendra et al (2017) in poults infected with MG.…”
Section: Resultssupporting
confidence: 81%
“…Infected poults with MG revealed insignificant decrease in IgA, IgG and IgM allover experimental period post infection Mycoplasma infection induced reduction in immune-globulin (Romero et al, 2001). Same change in immunoglobulin was reported by Wijesurendra et al (2017) in poults infected with MG.…”
Section: Resultssupporting
confidence: 81%
“…A GapA + clone, strain ts-304, has been isolated from ts-11 and has been shown to be as safe in chickens as the ts-11 strain from which it was derived, and as effective, but at a lower dose ( 21 , 22 ). The ts-304 vaccine has also been shown to colonize the trachea of turkeys and protect against experimental challenge with the M. gallisepticum wild-type strain Ap3AS ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research demonstrated that MG vaccination in turkeys and chickens produced a high antibody titer including increased CD4 + and CD8 + expressing lymphocytes in trachea. This suggested that these cells contributing toward the pathogenesis of the disease ( Wijesurendra et al., 2017 ). Therefore, agents which enhance the production of humoral immune response including lymphocytes production could be considered for the possible protection trial of MG infection in future studies.…”
Section: Discussionmentioning
confidence: 99%